A new 103Rh Unresolved Resonance Region evaluation. (August 2023) - Barry, D.P.; Lewis, A.M.; Leal, L.; Brown, J.M.
Abstract: A new evaluation in the Unresolved Resonance Region has been performed for 103 Rh, an important fission product. The evaluation was done in coordination with and is consistent with a new Resolved Resonance Region evaluation. It was determined using measured total cross section data that there is significant structure in the underlying dilute-average cross section within the unresolved resonance energy range of the evaluation (8–40.146 keV). Energy-dependent strength functions are provided to more accurately represent this structure. A covariance matrix for the average parameters that represent the entire Unresolved Resonance Region is provided to comply with the current ENDF-6 format. This new evaluation more closely matches the experimental data available when compared to the current evaluations. Highlights: A new 103 Rh evaluation was performed for the Unresolved Resonance Region (URR) in the energy range from 8 keV to 40.146 keV. The new 103 Rh URR evaluation takes into account structure in the underlying dilute-average cross section. Energy-dependent URR average parameters for 103 Rh are provided along with a covariance matrix.